The Influence of Lifestyle, Product Price, Quality, and Brand on Interest in Buying Second Branded Clothing in STIKES MAHARDIKA Students - Fardhoni (PT Inovasi Pratama Internasional, 2020)
This study aims to determine the effect of lifestyle , product price, quality and brand on the intention to buy second branded clothing among STIKES Mahardika students . This type of research is associative quantitative research and distributes questionnaires through a Google form platform to respondents who are sampled for this study and then the data is processed using SPSS ( Stasticical Product and Service Solution ) version 25.00. This study used a sample of 34 respondents. Sampling using purposive sampling technique . The test tools used are instrument test, classic assumption test and hypothesis test. From the results of this test it can be concluded that based on the results of the analysis of the first hypothesis it can be seen that t count ( 0.960 ) < t table ( 2.042 ), as well as with a significance value of 0.345 <0.05 it can be concluded that the first hypothesis is rejected, meaning that the variable Lifestyle (X1) has no significant effect on Purchase Intention (Y). The second hypothesis can be seen that t count ( 2.064 ) > t table ( 2.042 ), and the significance value is 0.048 <0.05, so it can be concluded that the second hypothesis is accepted, meaning that Product Price (X2) has an effect on Purchase Intention (Y).